PENGARUH KOMPETENSI KESELAMATAN DAN KESEHATAN KERJA SERTA KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA RUMAH SAKIT UMUM DAERAH WANGAYA KOTA DENPASAR - I Dewa Ayu Intan Wulandari; Gde Bayu Surya Parwita; Putu Agus Eka Rismawan (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
Performance is the quality of work achieved by an employee which in this study has decreased. This study aims to examine the effect of competence, occupational safety and health and organizational commitment on employee performance at the Wangaya Regional General Hospital, Denpasar City. This research was conducted at the Wangaya Regional General Hospital, Denpasar City, using a sample of 82 employees. The sampling technique used in this study was the accidental sampling method. Data was collected through interviews and questionnaires. The data analysis technique used in this study was multiple linear regression analysis which was processed using the Statistical Package Social Science (SPSS) version26. The results showed that competence and organizational commitment had a positive and significant effect on employee performance, while occupational safety and health had no direct effect on employee performance. The thing that must be improved is to always carry out training by regulating the air temperature in the workplace in order to be able to increase the sense of belonging of an employee. Future research is expected not to rely on the factors in this research,but can add other factors that may affect employee performance.Keywords: competence, occupational safety and health as well as organizational commitment, employee performance